Evaluasi Fasilitas dan Aksesibilitas pada Gedung Kantor BPJS kesehatan Sleman - Adena Putri Br Surbakti (Universitas Diponegoro, 2024)
User diversity in a public building brings up the diversity of user needs. In providing user needs, universal design is the correct answer. However, the importance of universal design’s application to create an environment without physical boundaries, age, or gender has not yet been widely realized. Therefore, the need for activities in a building is often not fulfilled, especially for people with disabilities. This also occurs in most office buildings in Indonesia, where the facilities and accessibility provided by offices do not yet meet universal design standards. Facilities and accessibility are among the things that should be considered to ensure that activities carried out within buildings are not hindered. This research aims to evaluate the facilities and accessibility in the BPJS Health Office building in the Sleman branch to determine its compliance with universal design standards.The method applied in this research is a quantitative descriptive approach and evaluative analysis. The data analyzed consists of site data and building data related to the design object in the form of Detailed Engineering Design (DED) drawings. The results of this research indicate that several facilities are already available in the BPJS Sleman Office building, including doors, corridors, ramps, stairs, toilets, and parking areas. However, the facilities and accessibility in the building are not fully compliant with the standards outlined in Ministerial Regulation PUPR No. 14 of 2017 concerning Building Accessibility Requirements. Therefore, recommendations are needed regarding adjustments to the facility and accessibility needs in the BPJS Sleman Office building based on the standards outlined in Ministerial Regulation PUPR No. 14 of 2017.